Obesity-associated hypertension among primary school children in Sarawak: a cross-sectional study - Cheah, WL; Helmy H,; Roslinda K,; Mohd Taha A,; Ayu Akida AR, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Hypertension has been recognised as an important public health issue, affecting paediatric population. This study aimed to determine the prevalence of hypertension and its relationship with obesity among different ethnic, gender primary school children in Kuching division, Sarawak. It was a cross-sectional study using multistage sampling. Data was collected using anthropometric equipment and digital blood pressure monitor. Data was analysed using SPSS version 20. A total of 1314 respondents participated. 36.9% of the respondents were overweight and obese, 31% were overfat and obese, 29% had abnormal waist circumference and 32.8% had abnormal waist-height ratio (WHtR). About 22.1% of the respondents were found to be in pre-hypertension and hypertension stage. There were significant differences in overweight and obese, overfat and obese, WHtR between males and females. Indigenous Sarawak reported to have the highest number of hypertensive at risk, overweight and obese, overfat and obese, abnormal waist circumference and WHtR. Those respondents who were hypertensive were found to be overweight and obese, overfat and obese, with abnormal waist circumference and WHtR. Screening of potential risk factors at a young age would help to reduce the incidents of chronic disease in the adulthood. Blood pressure measurement should be included in the routine physical examination, to identify high risk children for further investigation.